Microwave Synthesis of Some New 1,3-Oxazepine Compounds as Photostabilizing Additives for Poly(vinyl chloride) Films - Salih, Nadia; Salimon, Jumat; Yousif, Emad; Hamed, Ayad (Asian Journal of Chemistry, 2013)
The work presented the synthesis of four new compounds containing 1,3-oxazepine and 1,3,4-oxadiazole [I-IV] by microwave assisted organic synthesis method through the condensation reaction of 2-[4-(arylidene)phenyl-1,3,4-oxadiazole-5-thiol] with maleic anhydride under variable microwave power (180, 510) watt. The structure of the synthesized compounds was characterized using available spectroscopic methods (1H-NMR, FTIR). The photo stabilization of poly(vinyl chloride) films by using 3-oxazepine and 1,3,4-oxadiazole compounds was investigated. The PVC films containing concentration of complexes 0.5 % by weight were produced by the casting method in tetrahydrofuran. The photostabilization activities of these compounds were determined by monitoring the carbonyl, polyene and hydroxyl indices with irradiation time. The changes in viscosity average molecular weight of PVC with irradiation time were also tracked (using THF as a solvent). The quantum yield of the chain scission (Fcs) of these complexes in PVC films was evaluated and found to range between 4.27 × 10-8 and 7.41 × 10-8. Results showed that the rate of photostabilization of PVC in the presence of the additive followed the trend: I > II > III > IV. According to the experimental results, several mechanisms were suggested depending on the structure of the additive. Among them, UV absorption, peroxide decomposer and radical scavenger for photostabilizer mechanisms were suggested.